Stability of Sources of Resistance to Cowpea Aphid (Aphis craccivora Koch, Hemiptera: Aphididae) across Major Cowpea Production Zones in Ghana. (15th July 2020) - Kusi, Francis; Nboyine, Jerry A.; Attamah, Patrick; Awuku, Justice F.; Sugri, Issa; Zakaria, Mukhtaru; Lamini, Salim; Mensah, Gloria; Larweh, Victoria; Owusu, Robert K.; Agyare, Richard Y.; Yirzagla, Julius; et al.
Abstract : Aphids ( Aphis craccivora Koch) are an important vegetative stage pest of cowpea in Africa. The use of resistant cultivars is among the best management option for this pest, but the success of this strategy is influenced by the stability of the resistant genotype to the cowpea aphid biotypes present in the major cowpea growing areas in a country. This work, therefore, aimed at identifying cultivars/genotypes with stable resistance to aphid infestation across different cowpea growing ecologies in Ghana and estimating yield loss due to aphid infestation at the seedling stage. To ascertain the stability of aphid-resistant cultivars/genotypes, four cultivars/genotypes (SARC1-57-2, SARC1-91-1, IT97K-499-35, and Zaayura) and a susceptible check (Apagbaala) were tested across 18 locations in Ghana. An on-station experiment was used to quantify yield losses due to aphid attack at the seedling stage in the five cultivars/genotypes mentioned above together with 5 additional cultivars/genotypes [i.e., IT99K-573-3-2-1, IT99K-573-1-1, Padituya, Resistant BC4 F3 (Zaayura//(Zaayura × SARC1-57-2)), and Susceptible BC4 F3 (Zaayura//(Zaayura × SARC1-57-2))]. The results showed that SARC1-57-2 was stable in all ecologies, in terms of its resistance to aphids; it had high vigour score (3.8 ± 0.03) and low plant mortality (3.7 ± 0.22%) compared to the susceptible genotypes. The number of days to flowering and maturity were significantly higher in aphid-infested plants than in the uninfested ones. Grain yield loss was estimated to range between 3.8 and 32.8%. Except for SARC1-57-2, Resistant BC4 F3, and Padituya, the remaining cultivars/genotypes sustained significant yield losses under aphid infestation. Thus, the aphid-resistance gene in SARC1-57-2 is stable against aphids. This resistance genotype can be incorporated into cowpea improvement programmes to breed for aphid-resistant cultivars. Also, the cultivation of such improved cultivars will reduce pesticide usage in cowpea production.